Verifying Self-Determination Theory in EFL Context: Considering the Relationship between Innate Needs and Motivation - Elham ZARFSAZ; Fahime sadat Hosseini (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
Self-Determination Theory (SDT) is a hot topic in the field of applied linguistics, and it is getting more and harder to downplay the significance of the so-called theory in the growth of second-language learners (Deci and Ryan, 1985, 2000, 2002). The current study tried to test the theory in the Iranian EFL setting by throwing light on the relationship between innate or basic psychological requirements of competence, relatedness, and autonomy and (intrinsic) motivation. This was done as a commentary on other research findings. 324 EFL university students from Iran were contacted to take part in the study. A standard questionnaire created by Agawa and Takeuchi (on the students' motivation for learning a second language and their innate needs fulfillment) was used to collect data for the survey-style study (2016). SEM, or structural equation modeling, was used to determine how well actual data matched hypothetical expectations. According to the SEM model suggested, there was a strong positive correlation between Iranian EFL learners' motivation and their competency demands. However, relatedness needs appeared to have less of an impact on students' motivation, while the satisfaction of autonomy needs was found to have either adverse or demotivating impacts on Iranian L2 learners' motivation. These findings can be applied to improve second language learners' motivation by posing engaging questions about the nature of the students' demands for autonomy, relatedness, and competence.